Performance of Egsb Reactor Using Natural Zeolite as Support for Treatment of Synthetic Swine Wastewater - Huilinir-Curio, C; Montalvo-Martinez, S (Elsevier Ltd, 2021)
An expanded granular sludge bed (EGSB) reactor using natural zeolite as support was evaluated for treating synthetic swine wastewaters. The process was operated at 30 °C during 255 days in two reactors at laboratory scale. The control reactor (Rc) was operated only with granular sludge while 120 g of zeolite was supplemented additionally in the other reactor (Rz). The anaerobic processes were developed with organic loading rate (OLR) up to 15 kgCOD/m3 d and different up-flow velocities (vup) were applied (6, 10 m/h). An operation up to 10 kgCOD/m3 d at 6 m/h no significant differences were found between reactors, but at 10 m/h and 15 kgCOD/m3 d, the zeolite-EGSB reactor provides a more stable process, with 89.1% of COD removal efficiency and less than 1 g/L of volatile fatty acids (VFAs) accumulation. Differences in granule formation and size as well as the populations of Bacteria and Archaea between the two reactors demonstrated the positive influence of zeolite addition. © 2020 Elsevier Ltd.